THE SOLAR ECLIPSE EFFECT ON DIFFUSION PROCESSES OF O+ + O2 ? O2+ + O REACTION FOR THE UPPER IONOSPHERE OVER KHARKOV - Yasar, Mehmet (Vinca Inst Nuclear Sci, 2021)
The Sun is the most elective factor in determining all processes in the ionosphere. For this reason, examining the effect of solar eclipses on the earth ionosphere provides a very important source of information about sudden and medium-scale changes in the ionosphere structure during a solar eclipse. In this study, the effect of solar eclipse on March 29, 2006 in Kharkov on self-diffusion of O+ + O-2 -> O-2(+)+ O reaction was investigated depending on the altitude (202, 252, and 303 km). As a result of the investigation, the minimum value of self-diffiision coefficient was seen at three altitudes on March 29, 2006 at the time of full covering in the solar. Self-diffusion coefficients were found to increase with increasing altitude. The results of the experimental study conducted to examine the effect of the eclipse on the ionosphere using high frequency wave propagation in Turkey where it was seen total eclipse on March 29, 2006 and the result that we obtained in this research are consistent with each other.
Keywords: ionosphere; chemical reactions; Kharkov incoherent scatter radar; solar eclipse; diffusion